The Effect of Media Exposure, Profitability, and Green Accounting on Corporate Social Responsibility Disclosure in Healthcare Sector Companies Listed on the Indonesia Stock Exchange for the 2021–2024 Period - Novi Jelpiani M Hutagalung; Mulatua P Silalahi; Merry Anna Napitupulu; Sahala Purba (Program Studi Akuntansi Universitas Simalungun, 2026)
This study aims to examine and analyze the influence of Media Exposure, Profitability, and Green Accounting on Corporate Social Responsibility (CSR) Disclosure in healthcare sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. Using a quantitative research approach with purposive sampling, this study obtained 12 companies from a population of 38 healthcare companies as the final sample. Data were analyzed using multiple linear regression with IBM SPSS Statistics version 26. The results show that partially, Media Exposure has a negative and significant effect on CSR Disclosure (β = -0.156, Sig. = 0.007), while Profitability has a positive but insignificant effect on CSR Disclosure (β = 0.022, Sig. = 0.861), and Green Accounting has a negative and insignificant effect on CSR Disclosure (β = -0.516, Sig. = 0.520). Simultaneously, the three independent variables (Media Exposure, Profitability, and Green Accounting) do not have a significant effect on CSR Disclosure (F = 2.801, Sig. = 0.052). The coefficient of determination (Adjusted R²) is 10.9%, indicating that 89.1% of the variation in CSR Disclosure is explained by other factors outside this model. These findings contribute to the literature by highlighting the unique characteristics of the healthcare sector—particularly during the COVID-19 pandemic transition period—in shaping corporate sustainability reporting behavior